A reconstruction method of electron density distribution in the equatorial region of magnetosphere - Shastun, V.V.; Agapitov, O.V. (Advances in Astronomy and Space Physics, 2015)
A method for the estimation of electron density from the ratio of the wave magnetic and electric field amplitude of whistler waves is developed. Near the geomagnetic equator, whistler wave normals are mainly close to the direction of the background magnetic field. Dispersion relation of whistler wave in the parallel propagation approximation is used in this method. Signals registered by STAFF-SA instrument on board the Cluster spacecraft are used for electron density reconstruction. The Cluster spacecraft crossed the plasmasphere at all local times and in a wide range of latitudes over 10 years (2001-2010) overing well the frequency range of both plasmaspheric hiss and lower band chorus emissions in a vicinity of the geomagnetic equator. The proposed technique can be useful in allowing to supplement plasma density statistics obtained from recent probes (such as THEMIS or Van Allen Probes), as well as for reanalysis of statistics derived from continuous measurements of only one or two components of the wave magnetic and electric fields on board spacecaft covering equatorial regions of the magnetosphere.